Calcineurin, the Ca(2+)-dependent phosphatase, regulates Rga2, a Cdc42 GTPase-activating protein, to modulate pheromone signaling - Ly, Nina (Mol Biol Cell, 2017)
Calcineurin, the conserved Ca(2+)/calmodulin-activated phosphatase, is required for viability during prolonged exposure to pheromone and acts through multiple substrates to down-regulate yeast pheromone signaling. Calcineurin regulates Dig2 and Rod1/Art4 to inhibit mating-induced gene expression and activate receptor internalization, respectively. Recent systematic approaches identified Rga2, a GTPase-activating protein (GAP) for the Cdc42 Rho-type GTPase, as a calcineurin substrate. Here we establish a physiological context for this regulation and show that calcineurin dephosphorylates and positively regulates Rga2 during pheromone signaling. Mating factor activates the Fus3/MAPK kinase, whose substrates induce gene expression, cell cycle arrest, and formation of the mating projection. Our studies demonstrate that Fus3 also phosphorylates Rga2 at inhibitory S/TP sites, which are targeted by Cdks during the cell cycle, and that calcineurin opposes Fus3 to activate Rga2 and decrease Cdc42 signaling. Yeast expressing an Rga2 mutant that is defective for regulation by calcineurin display increased gene expression in response to pheromone. This work is the first to identify cross-talk between Ca(2+)/calcineurin and Cdc42 signaling and to demonstrate modulation of Cdc42 activity through a GAP during mating.